2003
DOI: 10.1002/jrs.988
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of iron protoporphyrin IX chloride in ionic detergent micelles probed by resonance Raman spectroscopy

Abstract: Photoinduced electron transfer from axially coordinated electron donor to hemin in aqueous cetyltrimethylammonium bromide and sodium dodecyl sulfate micelles under various pH conditions with and without hindered/unhindered imidazoles was investigated. Photoreduction of hemin in the former micelles under anaerobic conditions in alkaline and neutral aqueous medium takes place by electron transfer from axially coordinated hydroxyl ion to an FeIII atom in the photoexcited state. In sodium dodecyl sulfate micelles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The UV/vis spectrum of a heme−DDAB solution is similar to the UV/vis spectrum of a myoglobin−DDAB solution showing the Soret (∼395 nm), Q (∼569 nm), and CT1 (∼600 nm) bands at similar wavelengths, which suggests that the species in both solutions are equivalent. This species most likely is a heme group in a micellar environment, since similar wavelengths were found for the Soret, Q, and CT1 bands of heme groups incorporated in cetyltrimethylammonium (CTAB) (400, 576, and 600 nm) and Triton X-100 (398, 576, and 600 nm) micelles. , In the case of DDAB this micellar environment probably does not consist of micelles, but consists of vesicles . These results show that DDAB can induce heme release from myoglobin and therefore support our voltammetric results.…”
Section: Resultssupporting
confidence: 85%
“…The UV/vis spectrum of a heme−DDAB solution is similar to the UV/vis spectrum of a myoglobin−DDAB solution showing the Soret (∼395 nm), Q (∼569 nm), and CT1 (∼600 nm) bands at similar wavelengths, which suggests that the species in both solutions are equivalent. This species most likely is a heme group in a micellar environment, since similar wavelengths were found for the Soret, Q, and CT1 bands of heme groups incorporated in cetyltrimethylammonium (CTAB) (400, 576, and 600 nm) and Triton X-100 (398, 576, and 600 nm) micelles. , In the case of DDAB this micellar environment probably does not consist of micelles, but consists of vesicles . These results show that DDAB can induce heme release from myoglobin and therefore support our voltammetric results.…”
Section: Resultssupporting
confidence: 85%
“…The Raman spectroscopy and photochemistry of metalloporphyrins have been studied extensively over the years. ,,,,,,, The vibrational bands exhibiting substantive changes in the photoproduct spectrum reported here are well-known to correlate with the oxidation state, spin state, and ligation of the iron atom in the porphyrin compound. In response to changes in the population of the different d-orbitals the metal atom may move in or out of the plane of the porphyrin ring, and the porphyrin core may expand or contract around the metal atom.…”
Section: Discussionmentioning
confidence: 85%
“…In the work reported here, resonance Raman and transient absorption (TA) spectroscopies are used to investigate the low-temperature excited state electronic dynamics and photochemistry of iron(III) tetraphenylporphyrin chloride [Fe (III) TPPCl]. Raman spectra obtained with 413 nm Soret band excitation at 77 K show both a solvent and power dependence that has yet to be elucidated in the literature. This photochemistry is also distinct from the electron transfer processes investigated with ultrafast spectroscopy in synthetic metalloporphyrins. The power dependence in Fe (III) TPPCl at 77 K indicates photochemistry in which at least three Fe (III) products are formed. The formation of all three photoproducts is well described by a 2-photon model based on light absorption from an excited electronic state with a ca.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of resonance Raman spectra of catalase or monooxygenase bioimitators, PPFe 3+ OH/Al 2 O 3 and penta-FTPhPFe 3+ OH/Al 2 O 3 showed that the frequencies ν 4 , ν 3 , ν 2 , ν 37 , ν 10 correspond to the values 1372, 1491, 1574, 1593 and 1631 cm −1 [10,12], which are characteristic of iron porphyrin catalase [16], and that the high-spin heme ion Fe 3+ is present in the fifth coordination position (Fig. 9).…”
Section: Study Of the Structure And Physicochemical Properties Of Sup...mentioning
confidence: 99%
“…The decrease in the frequency ν 4 of the complex to a value of 1361 cm −1 during the reduction of the complex indicates the involvement of the π-donor axial ligand of the iron ion in the form of Fe 3+ -O-Al. Thus, a pronounced analogy with the sixth coordination high-spin heme ion Fe 3+ associated with tyrosine in catalase is revealed [12,16].…”
Section: Study Of the Structure And Physicochemical Properties Of Sup...mentioning
confidence: 99%